IMPACT OF COMPENSATION MANAGEMENT ON PERFORMANCE OF TECHIES IN IT COMPANIES - Reddy, Dr. D. Harikishan (The journal of contemporary issues in business and government, 2023)
This research article aims to “To study the impact of compensation management attributes on performance of techies”. The paper applies data reduction using Exploratory Factor Analysis (EFA) on a sample of 274 respondents drawn from IT companies in the Bengaluru and condenses a set of 14 compensation management statements converted into a four attributes. The present study proposes a model of the impact of compensation management attributes on performance of techies. The present study proposes a model of the impact of compensation management attributes on performance of techies. The study found that pay, recognition, recreational facilities and awards are impacting significantly the performance of techies. Therefore, managers of IT companies should focus on the above factors to improve compensation. The study investigated the impact of compensation management attributes on performance of techies. Multiple linear regression analysis highlights that pay, recognition, recreational facilities and awards have significant impact on performance of techies.